1992
DOI: 10.1002/hep.1840160332
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystolithiasis: Lithotherapy for the 1990s

Abstract: Cholelithiasis afTects from 10% to 15% of the adult population in industrialized Western countries, with higher prevalence in women, in women with high parity, in the obese, in patients with hypertriglyceridemia and in older patients (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). In the United States, it has been estimated that 20 to 25 million people have gallstones, and more than 500,000 cholecystectomies are performed annually. Cholecystectomy is the most frequently performed surgical procedure, after cesarea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 191 publications
(147 reference statements)
1
23
0
Order By: Relevance
“…As for diagnostic approach, abdominal X-ray was not performed in all cases; in fact, radiographic aspect of gallstones in a third of patients was not evaluated. As for treatment, although in adults UDCA therapy is recommended only for a specific subset of patients [15] , in the present study this drug was used in about two third of cases and only in half of cases the gallstones were radiolucent. Our study confirmed that UDCA was ineffective in dissolution of gallstones in the vast majority of the cases.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…As for diagnostic approach, abdominal X-ray was not performed in all cases; in fact, radiographic aspect of gallstones in a third of patients was not evaluated. As for treatment, although in adults UDCA therapy is recommended only for a specific subset of patients [15] , in the present study this drug was used in about two third of cases and only in half of cases the gallstones were radiolucent. Our study confirmed that UDCA was ineffective in dissolution of gallstones in the vast majority of the cases.…”
Section: Discussionmentioning
confidence: 69%
“…The non-surgical approach is based on the use of ursodeoxycholic acid (UDCA); UDCA can reduce cholesterol saturation in bile and progressively dissolve cholesterol gallstones [13,14] . Treatment of radiolucent gallstones with UDCA has been well documented in adults [15][16][17] ; on the contrary, little information is available for children [18,19] . Another approach to pediatric cholelithiasis is represented by expectant management, in which the patients are not treated with medical or surgical therapies but are followed up with periodical clinical and ultrasound controls.…”
Section: Resultsmentioning
confidence: 99%
“…At recurrence, 48% of patients had solitary gallstones while 52% had multiple gallstones. The number of recurrent gallstones (i.e., solitary or multiple) was concordant with the initial gallstone number only in 44% and 46% of the cases Table 1 for previous criteria, 27 was higher in patients with than without the definition of the two apoE groups. recurrence (53% vs. 13%, P Å .001).…”
Section: Aid Hepa 0041mentioning
confidence: 61%
“…Symptomatic gallstone disease was defined according to accepted criteria as a clinical history with typical biliary pain. 15 In Chile some gallbladder bile from nongallstone patients (n ϭ 6) was also obtained. These patients underwent surgery because of resectable gastric cancer.…”
Section: Methodsmentioning
confidence: 99%